Effect of Social Media Marketing on Visit Intention and Willingness to Pay Premium Price for Ecotourism - Sadu, I Gede Darma; Tan, Kevin Reagan; Setiawan, Nadya Permata; Hendriana, Evelyn (Journal of Management Economic and Financial, 2024)
Demand for ecotourism is increasing due to higher awareness of environmental damage and the hype in social media. To minimize over-tourism, the government is considering charging higher prices for ecotourism destinations that may cause a decline in the number of visitors. While the Theory of Planned Behavior (TPB) has been frequently used to explain tourists’ visit intention, it has not integrated the perceived social media marketing as the determinant of its antecedents and looked at the subsequent impact of visit intention, such as willingness to pay premium price. This study aims to examine the effect of perceived social media marketing on visit intention and willingness to pay premium price by using TPB as its theoretical basis and Komodo National Park as a study context. Data from 265 millennial and Generation Z tourists were tested using PLS-SEM that showed significant effects of perceived social media marketing on attitude toward the destination, subjective norms, and destination image, which together with perceived behavioral control subsequently affected visit intention. Finally, visit intention stimulates tourists’ willingness to pay a premium price to visit the destination.